2005
DOI: 10.1093/nar/gki857
|View full text |Cite
|
Sign up to set email alerts
|

UVA-visible photo-excitation of guanine radical cations produces sugar radicals in DNA and model structures

Abstract: This work presents evidence that photo-excitation of guanine radical cations results in high yields of deoxyribose sugar radicals in DNA, guanine deoxyribonucleosides and deoxyribonucleotides. In dsDNA at low temperatures, formation of C1′• is observed from photo-excitation of G•+ in the 310–480 nm range with no C1′• formation observed ≥520 nm. Illumination of guanine radical cations in 2′dG, 3′-dGMP and 5′-dGMP in aqueous LiCl glasses at 143 K is found to result in remarkably high yields (∼85–95%) of sugar ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

52
308
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 67 publications
(363 citation statements)
references
References 49 publications
52
308
3
Order By: Relevance
“…[24][25][26][27] It was found that excited DNA base cation radicals formed high yield of sugar radicals which confirmed the proposed hypothesis. [24][25][26][27] While strand breaks are biologically significant, it is combinations of DNA damages known as multiple damage sites (MDS) that are the most lethal type of DNA damage. Such combinations of single-and double-strand breaks and base damages with 10 base pairs are known to lead to irreparable damage because of the loss of local structural information.…”
supporting
confidence: 73%
See 4 more Smart Citations
“…[24][25][26][27] It was found that excited DNA base cation radicals formed high yield of sugar radicals which confirmed the proposed hypothesis. [24][25][26][27] While strand breaks are biologically significant, it is combinations of DNA damages known as multiple damage sites (MDS) that are the most lethal type of DNA damage. Such combinations of single-and double-strand breaks and base damages with 10 base pairs are known to lead to irreparable damage because of the loss of local structural information.…”
supporting
confidence: 73%
“…þ to sugar radical formation (80-100%) was found, while with oligos of increasing length and DNA the yield was found to fall off to $50%. 24,26,27 This experimental observation was further supported by theoretical calculations using time-dependent density functional theory. [26][27][28] The excited states of G .…”
Section: Formation Of Sugar Radicals Via Photoexcitation Of One-electsupporting
confidence: 53%
See 3 more Smart Citations